Analisis yang Mempengaruhi Faktor Belajar dalam Materi Pelajaran IPS Kelas VII pada Kurikulum Merdeka SMP Negeri 1 Sitolu Ori T.A 2024/2025: Penelitian - Fani Riski Zega; Wahyutra Adilman Telaumbanua; Bezisokhi Laoli; Asali Lase (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aimed to analyze the factors causing learning difficulties in Social Studies (IPS) among seventh-grade students at SMP Negeri 1 Sitolu Ori in the 2024/2025 academic year. Learning difficulties were examined from both internal and external factors affecting students’ learning processes. This research employed a quantitative approach using a descriptive method. Internal factors included physical condition, psychological aspects, and fatigue, while external factors comprised family, school, and community environments. Data were collected through observation, questionnaires, and documentation. The research instruments were tested for validity and reliability. The sample consisted of seventh-grade students who experienced a decline in academic achievement. The results indicated that students’ learning difficulties were influenced by both internal and external factors. Among internal factors, psychological aspects (10.0%) and fatigue (20.0%) were categorized as low, whereas physical factors (20.0%) were categorized as moderate. Regarding external factors, family (10.0%) and community (10.0%) influences were categorized as low, while school factors (30.0%) were categorized as moderate and identified as the most dominant factor affecting students’ learning difficulties. These findings highlight the crucial role of schools in creating a supportive learning environment to reduce students’ learning difficulties.